Cooperative Learning Model of Group Investigation Technique in Economic Learning - Nofriansyah, Nofriansyah; Rahayu, Sri; Wardiman, Jery (Journal of Economics and Economic Education, 2024)
This study aims to analyze the effect of cooperative learning models with Group Investigation techniques in learning economics. The research method used is a literature study by analyzing various relevant previous studies. The results showed that the Cooperative Learning Model of Group Investigation technique can improve student learning outcomes in economic learning. The conclusion of this study suggests the application of the Group Investigation technique in learning economics to improve the quality of education.